Solution of boundary value problem via C*-algebra valued bipolar metric spaces - Mohammad Imam Pasha; Kotha Rama Koteswara Rao; Kavitha Nallasamy; Gunaseelan Mani; Santosh Kumar (Applied General Topology)
In this manuscript, we prove common fixed point theorems using commuting mapping on C*-algebra valued bipolar metric space. Some of the well-known outcomes in the literature are expanded and generalized by the results shown. An example and applications to support our result is presented.